A computational investigation on the cyclohexylamine recognition using the pure and Cu-doped BN nanotube. Issue 4 (4th March 2023) - Kadhim, Mustafa M.; Taban, Taleeb Zedan; Abdullaha, Sallal A.H.; Al-Shati, Ahmed Salah; Rheima, Ahmed Mahdi; Hachim, Safa K.
ABSTRACT: We scrutinise the adsorption of cyclohexylamine (CHA) on pure and Cu-doped BN-nanotube (Cu@BN-NT) through density functional theory calculations. CHA had a weak interaction with the pristine BN-NT, making BN-NT not suitable to be used as a sensor. However, there was a substantial rise in the reactivity and sensitivity of the BN-NT after replacing the B with metal Cu, based on the standard Gibbs free energy of formation. There is a reduction in the energy gap of the HOMO–LUMO of Cu@BN-NT from 2.28 to 1.42 eV (∼ −37.7%) when CHA was adsorbed, which substantially increased the electrical conductivity. Hence, converting the substantial change in the electrical conductivity into an electronic signal was possible, which demonstrated that the Cu@BN-NT was an encouraging sensor to detect CHA. The computed recovery time for the Cu@BN-NT was 26.8 s, which is short.